Optimal planning and operation of multi-vector energy networks: A systematic review. (November 2020) - Hosseini, Seyed Hamid Reza; Allahham, Adib; Walker, Sara Louise; Taylor, Phil
Abstract: This paper provides a systematic review of recent publications on simulation and analysis of integrated multi-vector energy networks (rather than energy hubs) and carries this out through the lens of energy trilemma. This review is essential for energy research community to move forward in effective manner toward 2050 net zero carbon targets. This paper presents a holistic view of state-of-the-art of research in this field and identifies gaps in knowledge which should be addressed by future research urgently. Furthermore, this paper introduces a taxonomy of energy networks analysis, offering a unified description of findings of relatively large number of publications devoted to the subject. Moreover, this work analyses and classifies current research trends in the field of analysis of energy networks integration, and also identifies future trends in this field. This review serves as a guide to researchers regarding the main findings of energy networks integration evaluated through the lens of energy trilemma. The reviewed papers have been classified into three groups: (i) Operational analysis; (ii) Optimal dispatch; and (iii) Optimal planning. The focus of the paper is energy networks, since they play fundamental role in integrated energy systems and there is a lack of understanding of interactions and interdependencies between multi-vector networks. Also, focus of this paper has been on key findings of published research rather than details of individual energy models. The paper provides useful insights for energy research community by presenting several novel ideas for future research and facilitating the path to a decarbonised economy, due to the fulfilled comprehensive systematic review. Highlights: A total of 186 most recent papers on integrated multi-vector energy networks analysis are systematically reviewed. Findings of those papers were classified into three groups: operational analysis, optimal dispatch and optimal planning. In each group, different aspects of the three elements of energy trilemma were evaluated in detail. Several recommendations for future applied research priorities are presented. Useful insights for the energy research community are provided to facilitate the path to a decarbonised economy.